Hemodynamic effects of withholding vs. continuing angiotensin II receptor blockers on the day of prone positioning spinal surgery in elderly patients - Yuan, Ruimei; Xu, Min; Hu, Chunhai; Ma, Huailing; Meng, Fanjun; Ren, Jie; Wen, Jing (Frontiers in Medicine, 2024)
Introduction The hemodynamic effects of withholding vs. continuing angiotensin II receptor blockers (ARBs) before surgery in elderly patients undergoing spinal surgery in a prone position during anesthesia induction to skin incision are still unknown. Methods In this prospective study, 80 patients undergoing spinal surgery in a prone position with general anesthesia, aged 60–79 years, American Society of Anesthesiologists (ASA) II or III, were enrolled. Patients who had ARBs only in their preoperative medication list were randomly divided into two groups at a 1:1 ratio: In Group A, ARBs were continued on the morning of surgery, while in Group B, they were withhold. Norepinephrine was infused to maintain the blood pressure at the baseline level of ±20% during anesthesia induction in all patients. The primary outcome was the consumption of norepinephrine in each group from anesthesia induction to skin incision. The secondary outcomes include changes in invasive arterial blood pressure and heart rate, the fluid infusion volumes, the amounts of anesthetic drugs, and the total time from induction to skin incision. Results There were no significant differences in the demographics, the fluid infusion volumes, the amounts of anesthetic drugs, the total time from induction to skin incision, and hemodynamics at different time points (p > 0.05), while significant differences were found in norepinephrine consumption between the two groups (p < 0.001). Compared with Group B, the consumption of norepinephrine increased significantly in Group A (93.3 ± 29.8 vs. 124.1 ± 38.7 μg, p = 0.000). In addition, the same trend was illustrated in the pumping rate of norepinephrine between Group B (0.04 ± 0.01 μg·kg−1·min−1) and Group A (0.06 ± 0.02 μg·kg−1·min−1) (p = 0.004). Conclusion Our study conducted in elderly patients with hypotension undergoing prone spinal surgery demonstrated a greater pumping rate of norepinephrine during anesthesia induction in patients with ARBs continuing before surgery than those withholding, indicating that it was more difficult to maintain hemodynamic stability. Clinical Trial Registration: https://www.chictr.org.cn/showproj.html?proj=141081, ChiCTR2100053583.